Impact of Methotrexate and 7‐Hydroxymethotrexate Exposure on Renal Toxicity in Pediatric Non‐Hodgkin Lymphoma - Hao Bing; Yi Ma; Jiamin Xu; Qixian Ling; Yanlong Duan; Libo Zhao (Cancer Medicine)
ABSTRACT Background 7‐Hydroxymethotrexate (7‐OHMTX) is the main metabolite in plasma following high‐dose MTX (HD‐MTX), which may result in activity and toxicity of the MTX. Moreover, 7‐OHMTX could produce crystalline‐like deposits within the renal tubules under acidic conditions or induce renal inflammation, oxidative stress, and cell apoptosis through various signaling pathways, ultimately leading to kidney damage. The objectives of this study were thus to explore the exposure–safety relationship of two compounds and search the most reliable marker for predicting HDMTX nephrotoxicity. Method A total of 280 plasma concentration data (140 for MTX and 140 for 7‐OHMTX) for 60 pediatric patients with non‐Hodgkin lymphoma (NHL) were prospectively collected. Plasma MTX and 7‐OHMTX concentrations were determined using a high‐performance liquid chromatography tandem mass spectrometry (HPLC–MS/MS) method. A nonlinear mixed effect model approach was used to build a joint population pharmacokinetic (PopPK) model. After validation, the model estimated the peak concentration (Cmax) and area under the curve within the initial 48 h (AUC0‐48h) of the patients after drug administration by Bayesian feedback. The receiver operating characteristic (ROC) curves were generated to identify an exposure threshold associated with nephrotoxicity. Results A three‐compartment chain model (central and peripheral compartments for MTX and central compartment 7‐OHMTX) with the first‐order elimination adequately characterized the in vivo process of MTX and 7‐OHMTX. The covariate analysis identified that the aspartate aminotransferase (AST) was strongly associated with the peripheral volume of distribution of MTX. Moreover, the Cmax of MTX and 7‐OHMTX showed significant differences (p < 0.0001, p = 0.0472, respectively) among patients with or without nephrotoxicity. Similarly, individuals with nephrotoxicity also exhibited substantially higher ratio of 7‐OHMTX to MTX peak concentration and the sum of MTX + 2.25 times the concentration of 7‐OHMTX (p < 0.0001, p = 0.0426, respectively). By ROC analysis, the Cmax of MTX and 7‐OHMTX had the greatest area under the curve (AUC) values (0.769 and 0.771, respectively). A Cmax threshold of 9.26 μmol/L for MTX or a Cmax threshold of 0.66 μmol/L for 7‐OHMTX was associated with the best sensitivity/specificity for toxicity events (MTX: sensitivity = 0.886; specificity = 0.70; 7‐OHMTX: sensitivity = 0.886; specificity = 0.70). Conclusions We demonstrated that the Cmax of MTX and 7‐OHMTX were the most reliable markers associated with nephrotoxicity and proposed a Cmax threshold of 9.26 μmol/L for MTX and 0.66 μmol/L for 7‐OHMTX as the point with a high risk of nephrotoxicity. Altogether, this study may contribute to crucial insights for ensuring the safe administration of drugs in pediatric clinical practice.